Impact of nutrients and Mediterranean diet on the occurrence of gestational diabetes. Issue 1 (1st January 2021) - Mahjoub, Faten; Ben Jemaa, Houda; Ben Sabeh, Fatma; Ben Amor, Nadia; Gamoudi, Amel; Jamoussi, Henda
ABSTRACT: Background : The Mediterranean diet (MedDiet) is a dietary pattern effective in terms of prevention of many diseases such as gestational diabetes mellitus (GDM). Recently, many studies have paid attention to nutritional factors during pregnancy as a modifiable contributor to GDM risk. Objective : to investigate associations of nutrients intakes and MedDiet pattern of eating with risk of GDM. Subjects/Methods : This study conducted on N = 120; Pregnant women with GDM (n = 60) and without controls (n = 60). The dietary habits were assessed by a dietary history method and a validated food frequency questionnaire. We calculated a MedDiet score which measures the degree of adherence to a Med Diet. Result : A low Med Diet score was found in pregnant women with and without gestational diabetes in 46.7% and 38.8% of cases, respectively, with no significant difference. Our data showed that the higher the adherence score to the MedDiet, the lower the fasting blood glucose level and the plasma glucose 2 h post load. These findings concerned the two groups studied (P < 10 −3 ). We also noted that controls had a significantly higher intake of legumes, vegetables and fish. Monounsaturated fatty acids and saturated fatty acids consumption was significantly higher in the control group (2.3 ± 0.8 vs 1.7 ± 0.7, P < 10 −3 ). GDM subjects consumed significantly more dairy products and cereals (P < 10 −3 ). After adjustment for confounders, no nutrient was associated with the risk of developing gestational diabetes except vitamin D intake (OR 0.29 [0.15−0.54], P < 10 −3 ) which had a protective effect. Conclusion : Our study underlines the importance of adequate vitamin D intake during pregnancy and suggests that the MedDiet may reduce the incidence of gestational diabetes.